"What do we fear the most?": Exploring fears and concerns of patients, family members and dyads in end‐stage renal disease. Issue 4 (7th December 2020) - Frontini, Roberta; Sousa, Helena; Ribeiro, Óscar; Figueiredo, Daniela
Abstract: Introduction: End‐stage renal disease (ESRD) and the need for haemodialysis (HD) treatment are increasing. The course of the disease and all the life readjustments needed may generate a multitude of fears in patients and families. Aim: This study aimed to explore the main fears and concerns of patients with ESRD undergoing HD and their family members. Study design. A qualitative study was performed. Methods: Individual semi‐structured interviews were conducted with three groups: 20 patients, 14 family caregivers and 15 patient–family dyads. Interviews were audiotaped, transcribed verbatim and submitted to thematic analysis. Findings. Five major themes emerged: (i) fear of death (fear of earlier death, fear of a sudden death and fear of dying); (ii) fear of problems during HD (fears related to the vascular access, and fear of complications during HD); (iii) concerns related to the disease (fear of loss of autonomy, fears of getting worse, fears related to renal transplantation and concerns about dietary restrictions); (iv) fear about the future; and (v) absence of fears and concerns. Discussion: Patients with ESRD undergoing HD and their family members expressed different fears related to the disease and the treatments required. Renal care staff must acknowledge and understand such concerns and help patients and families to cope. This is important to improving people's quality of life (QoL), the dialogue between health professionals, patients, and family members, and the care offered by the dialysis care settings. Moreover, this study highlights the impact this disease has at a familial level. Future family‐based interventions should acknowledge possible fears and concerns of this population and integrate them into their programs.